Indirect assessment of dihydropyrimidine dehydrogenase activity in cats. (6th September 2013) - Saba, C. F.; Schmiedt, C. W.; Freeman, K. G.; Edwards, G. L.
Abstract: Use of 5‐fluoropyridimine antimetabolite drugs, specifically 5‐fluorouracil (5‐FU), has been discouraged in cats because of adverse events including neurotoxicity and death. Causes of toxicity have never been elucidated. In humans, toxicity has been associated with ineffective metabolism secondary to deficiencies in dihydropyrimidine dehydrogenase (DPD). Direct assessment of DPD activity is challenging; determination of uracil:dihydrouracil (U:UH2 ) in plasma using high performance liquid chromatography (HPLC) has been reported as an indirect measurement. U:UH2 was measured in the plasma of 73 cats. Mean U:UH2 for all cats was 1.66 ± 0.11 (median 1.53, range 0.24–7.00). Seventeen (23%) cats had U:UH2 >2, a value associated with decreased DPD activity in humans. Spayed female cats had significantly lower U:UH2 as compared with intact females, and age and U:UH2 were weakly but significantly negatively correlated ( r  = −0.26). Studies correlating U:UH2 and 5‐FU tolerability are required to further determine the validity and use of this test in cats.